Respuesta :

Answer:

f=

x

7x

2

+2x+6

+g

Step-by-step explanation:

Simplify 4×2 to 8.

2

+x−8+x+8−x+6x

2

+x+6 to 7{x}^{2}+2x+67x

2

+2x+6.

(f-g)x=7{x}^{2}+2x+6(f−g)x=7x

2

+2x+6

Then divide both side by x.

Finally add g to both sides

For this case we have the following expression:

[tex](f-g) (x) = x ^ 2 + x-4x ^ 2 + x + 4x ^ 2-x + 6x ^ 2 + x + 6[/tex]

We group similar terms:

[tex](f-g) (x) = x ^ 2-4x ^ 2 + 4x ^ 2 + 6x ^ 2 + x + x-x + x + 6[/tex]

We add taking into account that:

Equal signs are added and the same sign is placed

Different signs are subtracted and the major sign is placed.

[tex](f-g) (x) = 7x ^ 2 + 2x + 6[/tex]

Answer:

[tex](f-g) (x) = 7x ^ 2 + 2x + 6[/tex]